Bruton’s tyrosine kinase inhibition re-sensitizes multidrug-resistant DLBCL tumors driven by BCL10 gain-of-function mutants to venetoclax - Caroline A. Coughlin; Dhanvantri Chahar; Marianna Lekakis; Abdessamad A. Youssfi; Lingxiao Li; Evan Roberts; Natalia Campos Gallego; Claude-Henry Volmar; Ola Landgren; Shaun Brothers; Anthony J. Griswold; Catalina Amador; et al. (Blood Cancer Journal)
Abstract Disparate pathogenic mechanisms complicate precision-medicine efforts to treat diffuse large B-cell lymphoma (DLBCL), the most common lymphoma diagnosis. Though potentially curable with frontline combination chemoimmunotherapy, DLBCL carries persistently poor prognosis for those with relapsed or refractory (rel/ref) disease, despite recent advances in immunotherapy. Here, we build on recent findings implicating gain-of-function mutations in the BCL10 signaling protein as drivers of resistance to Bruton’s tyrosine kinase (BTK) inhibitors. We show mutant BCL10-driven DLBCL is resistant to multiple additional drug classes, demonstrating urgency to derive mechanistically rooted strategies to overcome undruggable BCL10 mutants that stabilize BTK-independent signaling filaments upstream of NF-kB activation. BCL10 mutants promote a cytokine-reinforced positive feedback loop of lymphomagenesis driving not just NF-kB but multiple additional pathways converging on diffuse activation of oncogenic transcription factors. Up-regulation of anti-apoptotic genes increases mitochondrial membrane potential, underlying multidrug resistance. Increased expression of BCL2, BCL2L1 (BCL-XL), and BCL2A1 (BFL1) drives resistance to venetoclax, but expression can be overcome by the potent non-covalent BTK inhibitor pirtobrutinib. Venetoclax plus pirtobrutinib synergized in overcoming resistance and potently killed BCL10-mutant lymphomas in vitro and in vivo. BTK therefore retains key roles protecting DLBCL from apoptosis even when downstream activation of the BCL10 signaling complex activates NF-kB independently.